Paciente femenino de 45 años de edad con derrame pleural asociado a síndrome nefrótico. - Soto Valenzuela, Juan José (2020)
The present study of this clinical case then refers to the health status in a 45-year-old female patient, who goes to the health facility for presenting a clinical picture characterized by dyspnoea that progresses from moderate to minimal effort, accompanied by coughing with whitish expectoration and peripheral edema, so immediate admission is required staying in the emergency area for 5 days. Several are the existing factors that lead an individual to suffer a pleural effusion, one of them, are people with kidney failure; in this case it is nephrotic syndrome, which represents a high risk, since there is an excessive increase in pleural fluid, it tends to alter respiratory physiology, resulting in the patient presenting significant symptoms in his breathing such as shortness of breath. Pleural Effusion represents a complication of great medical concern, once the diagnosis has been established either by chest x-ray and the respective physical examination, the treatment indicated by the specialist doctor is performed, the therapeutic includes oxygenation with low or high flow device to achieve maintain optimal ranges in oxygen saturation, as well as the treatment of the base disease such as dialysis sessions and diuretic administration. This clinical case study aims to approach respiratory care, providing the patient with pulmonary oxygenation that allows the correct alveolar ventilation, monitoring and monitoring its evolution, and thus avoiding other complications in their respiratory function.